Systemic toxicity of thiamethoxam in the mud crab (Scylla paramamosain): Oxidative stress, neurotoxicity, and growth retardation - Zhennan Wang; Ye Sun; Kaiming Luo; Shaolin Yao; Ce Shi; Changkao Mu; Chunlin Wang; Pingping Zhan; Yangfang Ye (Environmental Pollution, 2026)

The N-terminal region of pdm09/H1N1 PA synergizes with its cognate NP to enhance mammalian adaptation of avian-origin H9N2 canine influenza virus - Yefan Zhou; Pingping Wang; Shiqi Li; Fanyuan Sun; Min Zhu; Rang Wang; Shanshan Dong; Haodong Zhang; Yifeng Qin; Kang Ouyang; Yeshi Yin; Zuzhang Wei; et al. (Veterinary Microbiology, 2026)

Transcriptomic and proteomic analyses reveal mechanisms of long-term warming acclimation in Phaeocystis globosa - Dayong Liang; Ying Zhang; Huangxin Li; YingYing Wang; Jianping Sun; Zeyu Li; Hua Xiang; Pingping Shen (Harmful Algae, 2026)

Depth-dependent controls on soil saturated hydraulic conductivity in the Loess Plateau - Pingping Zhang; Yunqiang Wang; Hui Sun; Ruijie Li; Jingxiong Zhou; Laiming Huang (Journal of Hydrology, 2026)

Concentration and depth-resolved analysis of transition metals in atmospheric particles: A combined approach using X-ray fluorescence and synchrotron radiation single-particle imaging - Yiliang Liu; Jiawei Zhou; Hanxiong Che; Difei Zhang; Pingping Wen; Yifan Zhao; Xin Du; Lingshuo Meng; Yan Han; Zhier Bao; Xin Qi; Xin Long; et al. (Journal of Environmental Sciences, 2026)

Integrated data mining, network pharmacology and molecular docking to explore the medication rules and mechanism of traditional Chinese medicine compound in the treatment of acne - Wanyun Zhu; Ziyan Cheng; Qimei Xie; Bin Sun; Min Wei; Songfeng Wang; Yiyun Qian; Pingping Song (In Silico Pharmacology, 2026)

Isolation and identification of Fusarium sibiricum as a novel causal agent of root rot in Chamerion angustifolium - Tingting Zhang; Chengsong Liao; Lei Zhang; Zhengnan Li; Pingping Sun (Physiological and Molecular Plant Pathology, 2026)

Morphology, molecular identification, and pathogenicity of two Alternaria species associated with leaf spot of common bistort (Bistorta officinalis Delarbre) in China - Lin He; Jie Zhao; Jianxin Deng; Shanghua Liu; Lei Zhang; Zhengnan Li; Pingping Sun (Physiological and Molecular Plant Pathology, 2026)

Isolation and identification of two causal agents associated with root rot of Scutellaria baicalensis - Lin He; Qianci Chen; Pingping Sun; Lei Zhang; Honghong Jiao; Hongmei Cui; Yuan Yuan; Zhengnan Li (Physiological and Molecular Plant Pathology, 2026)

USP9X regulates copper-induced CASP9/CASP3/GSDME-dependent pyroptosis by deubiquitinating JAK1 - Huaduan Zi; Hengcheng Tang; Xiaoxi Yang; Xiaojin Li; Yanmeng Li; Anjian Xu; Qin Ouyang; Sisi Chen; Pingping He; Yanling Li; Qianyu Zhu; Bei Zhang; et al. (Apoptosis, 2026)

Light engineering in aquaculture: physiological responses of Takifugu rubripes larvae to controlled LED irradiance - Xin Li; Songtao Liu; Yafang Liu; Pingping Wei; Yanling Wu; Yingying Fang; Fei Sun; Ying Liu; Yumeng Wu; He Ma (Frontiers in Marine Science, 2026)
Introduction While indoor aquaculture has expanded globally, optimal lighting strategies for fish growth remain understudied. This study aims to establish optimal LED protocols for indoor-reared Takifugu rubripes larvae. Methods T. rubripes larvae were maintained at 50, 250, 500, and 750 mW/m 2 (i50, i250, i500, i750) from hatching through 30 DPH. Growth, gene expression, and enzyme activities were measured. Results Positive growth effects were observed at i250 and i500 within 14–17 DPH, while i50 caused complete mortality after 21 DPH. At 20 DPH, i500 upregulated IGF-1 and BMP2 expression, whereas i50 downregulated BMP4 and SOX9. i50 elevated CTSF, IGM, and HSP70, indicating stress. LPS activity was highest in i250 at 15 DPH, while LDH was lowest in i50. From 10–20 DPH, AKP and ACP were consistently lower in i50. During 5–20 DPH, SOD was suppressed in i750, while T-AOC increased in i250. Discussion Light conditions critically modulate enzymatic activity and early growth in T. rubripes larvae, though underlying mechanisms require further investigation.

Modeling and analysis of synthetic liquid fuel production from CO2 and nuclear energy using methanol-to-diesel process - Hernan E. Delgado; Pingping Sun; Vincenzo Cappello; Ana Gabriela Romero-García; Clarence Ng; Kwang Hoon Baek; Amgad Elgowainy; Richard D. Boardman; Jason Marcinkoski (Journal of Cleaner Production, 2026)

Subchronic exposure to decabromodiphenyl ethane impairs cognitive function and induces neuronal ferroptosis via disruption of mitochondria-associated endoplasmic reticulum membranes - Yuanteng Sun; Fei Xiong; Lingjie Wu; Zhihui Liu; Pingping Liu; Wenhao Li; Juan Zhang; Rongli Sun (Journal of Hazardous Materials, 2026)

Restoring aquaculture ponds to coastal wetlands using native vegetation reduces methane (CH4) production and emissions - Wenjing Liu; Hong Yang; Ping Yang; Qitao Xiao; Jujuan Gao; Lihua Wang; Chuan Tong; Yingzi Wang; Pingping Guo; Dongyao Sun; Yongxin Lin; Kam W. Tang (Agriculture, Ecosystems & Environment, 2026)

A 15,000-year Temperature record from the northern boundary of the east asian summer monsoon based on lacustrine brGDGTs - Nan Zhan; Zeyang Zhu; Pingping Li; Luo Wang; Ruilin Wen; Manman Xie; Qing Sun; Guoqiang Chu (Quaternary Science Reviews, 2026)

Variation in methane production since the last deglaciation reconstructed using isoprenoid GDGTs from the sediment of Sihailongwan Maar Lake in northeastern China - Pingping Li; Nan Zhan; Patrick Rioual; Guoqiang Chu; Guibin Zhang; Qi Li; Manman Xie; Guohui Lu; Qing Sun (Quaternary Science Reviews, 2026)

A robust estimation method for canopy chlorophyll content based on FOD and hierarchical weighting combination models - Jie Zhang; Xiaoyu Song; Yuanyuan Ma; Laigang Wang; Liang Sun; Li Li; Heguang Sun; Chunkai Zheng; Pingping Li; Xia Jing; Guijun Yang; Chunjiang Zhao (European Journal of Agronomy, 2026)

Transcriptome Analysis Reveals the Mechanism by which Probiotic Alleviate the Response of Juvenile American Shad (Alosa sapidissima) to High Temperatures - Chuwen Qiu; Chubing Gao; Pingping Deng; Zhuo Sun; Yongshi Liu; Jiabo Xu; Yonghai Shi (Probiotics and Antimicrobial Proteins, 2026)

Identification of a putative novel carlavirus infecting Gynura bicolor in China - Lei Xu; Mengze Guo; Pingping Sun; Lei Zhang; Zhengnan Li (Archives of Virology, 2026)

Large spatiotemporal variability in CH4 emissions from a subtropical coastal creek in southeast China affected by hydrological and biogeochemical processes - Lihua Wang; Ping Yang; Yingzi Wang; Pingping Guo; Derrick Y.F. Lai; Kwok Pan Chun; Chuan Tong; Dongyao Sun; Jiafang Huang; Guanpeng Chen; Hong Yang (Journal of Hydrology, 2026)

(Non)targeted analysis and environmental fate characterizing of novel organophosphorus flame retardants and plasticizers in dust samples from large-scale residential homes in China - Zijun Zhou; Zhipeng Cheng; Shaohan Zhang; Yiming Yao; Pingping Wang; Hongkai Zhu; Lei Wang; Hongwen Sun (Journal of Hazardous Materials, 2026)

NaCl and light quality reprogram carbohydrate metabolism to modulate growth, quality, and flavor in mustard (Brassica juncea) sprouts - Hongmei Di; Ling Li; Liping Su; Lisha Peng; Ling Rao; Zhifeng Chen; Victor Hugo Escalona; Jing Yang; Yu'nong Zhou; Yong Li; Xuena Yu; Kehao Liang; et al. (Food Chemistry, 2026)

The impact of anti-gout medications on eight cardiovascular diseases: a Mendelian randomized study - Pingping Peng; Jingting Wang; Miaozhen Huang; Congting Hu; Suyan Liu; Jia Liu; Jiaqin Cai; Xiaoxia Wei; Hong Sun (European Journal of Clinical Pharmacology, 2026)

Uncovering ecological risks of pesticides: From parent compounds to unknown transformation products in soils from Dongting Lake Basin - Lu Liu; Pingping Wang; Feng Li; Xiaoxiao Li; Meng Gao; Yiming Yao; Yu Wang; Zhipeng Cheng; Fei Ge; Hongwen Sun (Journal of Hazardous Materials, 2026)

Persistent luminescent nanoparticle-based immunochromatographic assay integrated with a smartphone device for simultaneous detection of aflatoxin B1 and T-2 toxin - Aimei Zhang; Mingzhu Liu; Jingran Sun; Zunquan Zhao; Yonghui Wang; Xiaoli Li; Jin Wu; Yanjun Fang; Pingping Zhang; Jialei Bai (Food Chemistry, 2026)

A Fiber-Driven Finite Element Model for Predicting Residual Limb Soft Tissue Deformation: Applications in Prosthetic Socket Design - Ling Wang; Ziyan Qiu; Lei Tang; Fuhao Huang; Pingping Wei; Senay Mihcin; Changning Sun; Hongyuan Zhao; Lei Shi; Song Han; Dichen Li (Annals of Biomedical Engineering, 2026)

Hydrological response to climate change and urbanization in a semi-arid urban river - Jiqiang Lyu; Yan Wang; Kexin Wang; Wenya Liu; Dongyong Sun; Pingping Luo; Zhaohui Zhou; Meng Jiao; Aidi Huo; Peng Guo (Urban Climate, 2025)

Na₂CO₃-SiO₂-H₂O nanofluids synergistically treats coal dust and hydrogen sulfide - Chunming Ai; Chang Liu; Pingping Sun; Chao Liu (Journal of Environmental Chemical Engineering, 2025)

Oligopeptide-loaded metal-organic framework nanocomposites promote regulatory T cell differentiation against periodontitis - Yu Wang; Xiaoqian Gong; Hongli Chen; Pingping Niu; Zhiduo Liu; Yao Sun (Chemical Engineering Journal, 2025)

Activating V4+/V5+ redox couple in polyanion lattice engineered Na3.1V2(PO4)2.9(SiO4)0.1-CNT by synergistic ionotronic strategy - Anyang Yu; Qi Fan; Zilong Fang; Tian Jiang; Xinxin Wang; Xiedie Zhao; Xiaoshuang Ma; Pingping Sun; Gang Li; Shijun Yuan; Haiyang Zhang; Yining Wang; et al. (Chemical Engineering Journal, 2025)

Deciphering spatial pattern and environmental drivers of deep soil moisture security: insights from integrating spatial non-stationarity in large-scale analysis - Yongping Tong; Yunqiang Wang; Zimin Li; Pingping Zhang; Wei Hu; Jingxiong Zhou; Xiangyu Guo; Hui Sun; Alexis Comber; Ronny Lauerwald (CATENA, 2025)

Curcumin alleviates ovarian hyperstimulation syndrome in the rat model via inhibiting the nuclear factor kappa B/hypoxia-inducible factor-1α signaling pathway - Lilan Sun; Xiumei Zhuo; Dandan Qi; Hao Ma; Fanhua Kong; Pingping Sun; Yan Zhang; Peng Xue; Huagang Ma (Histochemistry and Cell Biology, 2025)

Endothelial SPRY1 deficiency associates with angiogenic-metabolic reprogramming in pulmonary arterial hypertension: a multi-omics analysis of bulk and single-cell transcriptomic profiles - Yanfei Mo; Desheng Wang; Zhenkun Deng; Pingping Zhao; Zhen Gou; Xiaoyun Sun; Yunrui Zhang; Yang Bai (Apoptosis, 2025)

Unraveling trapped air-suction interplay in hydraulic hysteresis: experimental insights and a state-dependent water retention model - Pingping Sun; Xiaohui Gan; Pan Chen; Maosheng Zhang; Ling Xu; Jun Jia; Mujia Wang (Journal of Hydrology, 2025)

Determinants of flash drought recovery rates: the role of precipitation patterns and surface heterogeneity - Zixuan Qi; Yuchen Ye; Lian Sun; Chaoxia Yuan; Yanpeng Cai; Yulei Xie; Guanhui Cheng; Pingping Zhang (Journal of Hydrology, 2025)

Coastal creeks as greenhouse gas hotspots: the role of nutrient availability and microbial activity - Guanpeng Chen; Jianuo Gao; Ping Yang; Wenjing Liu; Dongyao Sun; Yongxin Lin; Chuan Tong; Wenjing Tan; Pingping Guo; Hong Yang (Journal of Hydrology, 2025)

Lead toxicity to earthworms (Eisenia fetida) and their accumulation mechanisms in soil - Maodong Qi; Wenzhi Lei; Jingran Sun; Yaohui Mu; Pingping Wang; Suilong Ai; Muhammad Ashraf; Lixin Zhang (Environmental Geochemistry and Health, 2025)

Characterization of Cyhalofop-butyl metabolism and identification of resistance genes in Barnyardgrass (Echinochloa crus-galli (L.) P. Beauv.) - Penglei Sun; Liangliang Niu; Xianmin Lan; Pingping Chen; Haiyan Yu; Jingchao Chen; Hailan Cui; Xiangju Li (Pesticide Biochemistry and Physiology, 2025)

Oxidative damage induced by daily exposure to primary and emerging aromatic amines: Insights from large scale biomonitoring and cell-based high-throughput PCR array analysis - Shaohan Zhang; Zijun Zhou; Pingping Wang; Yanan Yao; Yuhao Cao; Jialan Liu; Ping Li; Tao Zhang; Hongkai Zhu; Lei Wang; Hongwen Sun; Zhipeng Cheng (Journal of Hazardous Materials, 2025)

Quantitative assessment of heat tolerance in new rice varieties through field survey during natural extreme heat events - Ting Sun; Tianhui Miao; Jianan Hu; Haoyang Zhou; Minglu Li; Jiayi Zhang; Yuanyuan Pan; Ran Bi; Shenghao Ye; Menglei Wei; Zeyu Wu; Guoqiang Li; et al. (European Journal of Agronomy, 2025)

How does land use transfer affect ecosystem services in Northwest China? - Pingping Zhou; Yuansheng Tian; Jun Zhai; Xiaoyan Song; Yi Li; Wenyi Sun (Ecological Engineering, 2025)

Expanding scales: Achieving prediction of van Genuchten model hydraulic parameters in deep profiles by incorporating broad in situ soil information in pedotransfer functions - Yongping Tong; Yunqiang Wang; Jingxiong Zhou; Xiangyu Guo; Ting Wang; Yuting Xu; Hui Sun; Pingping Zhang; Zimin Li; Ronny Lauerwald (Journal of Hydrology, 2025)

N6-methyladenosine reader YTHDF3-mediated CEBPA translation maintains genomic stability and stem cell function to prevent liver injury - Yaxu Liang; Weiwei Yu; Haifeng Sun; Dayu Wang; Zhibo Wang; Hailing Shi; Yang Cao; Zijie Zhang; Jun Liu; Zhongyu Zou; Jiangbo Wei; Tong Wu; et al. (Science China Life Sciences, 2025)

Water consumption turning point for Robinia pseudoacacia occurs at its middle stand age - Yali Zhao; Yunqiang Wang; Ruijie Li; Lijun Qi; Hui Sun; Pingping Zhang; Zimin Li (Plant and Soil, 2025)

Ox-LDL Induces Neuron Apoptosis and Worsens Neurological Outcomes in aSAH via Fas/FADD Pathway - Yabin Song; Chen Yu; Dandan Bo; Junqi Sun; Yong Wang; Pingping Chen; Hanming Wu; Linghong Hong; Zhennan Ye; Long Zhang; Diangui Zhou (Molecular Neurobiology, 2025)

Ecological Disturbance Caused by Land Use Change in the Karst Area, China: A Combined Structural and Functional Perspective - Zhongfa Zhou; Yaopeng Sun; Min Fang; Jianwei Sun; Pingping Yang; Jie Kong; Shengjun Ding (Chinese Geographical Science, 2025)

Salcastaniols A-G, seven undescribed diterpenoids with cholinesterase inhibitory activities from Salvia castanea Diels f. tomentosa Stib - Zhaoyue Dong; Pingping Wang; Qingju Liu; Feng Ju; Miaomiao Sun; Mohammad Mahmoud Nagdy; Fancheng Meng; Guowei Wang; Zhihua Liao; Min Chen (Phytochemistry, 2025)

Dual signal output detection of acetamiprid residues in medicine and food homology products via nanopore biosensor - Yao Li; Jiyuan Tu; Hong Wang; Kexin Luo; Pingping Xiao; Tangbin Liao; Guo-Jun Zhang; Zhongyue Sun (Food Chemistry, 2025)

Polyploid breeding of Saccharina japonica: Harnessing aposporous reproduction - Pingping Tian; Yan Li; Nianchao Xue; Weiwei Wang; Shuxiu Chen; Yanling Liu; Juan Sun; Guangjin Liang; Juping Zhao; Liang Shi; Nan Zhao; Xia Li; et al. (Aquaculture, 2025)

Temperature variability in northeastern China over the Past 2000 Years: Linkages with the Arctic oscillation and solar activity - Nan Zhan; Fangang Zeng; Qi Li; Manman Xie; Ruixia Hao; Li Pingping; Ruilin Wen; Luo Wang; Qing Sun; Guoqiang Chu (Quaternary International, 2025)

Life‐cycle greenhouse gas emissions associated with nuclear power generation in the United States - Jun Hong Clarence Ng; Pradeep Vyawahare; Pahola Thathiana Benavides; Yu Gan; Pingping Sun; Richard Boardman; Jason Marcinkoski; Amgad Elgowainy (Journal of Industrial Ecology, 2025)
Under the 2022 Inflation Reduction Act, tax credits of up to $3/kgH 2 are available to hydrogen producers if they generate emissions at levels below 0.45 kgCO 2 e/kgH 2 , spurring producers to explore how hydrogen production via electrolysis using electricity generated by nuclear power may qualify for such tax credits. With uranium as a primary fuel for nuclear power plants (NPPs) and no on‐site emissions, the upstream emissions associated with nuclear fuel supply chains largely determine the carbon intensity of nuclear energy. Using the GREET (Greenhouse gases, Regulated Emissions, and Energy use in Technologies) model, we evaluated the life‐cycle greenhouse gas (GHG) emissions of uranium production and the use of uranium to generate electricity in light water reactor (LWR) NPPs. We evaluated the process chemicals and energy inputs throughout the nuclear fuel supply chain to identify the major contributors to nuclear fuel cycle GHG emissions. Such emissions are estimated at 3.0 gCO 2 e/kWh at NPPs in the United States. The greatest share of nuclear fuel cycle GHG emissions—comprising 53% of total emissions—are associated with electricity consumption throughout the fuel supply chain. We extended the analysis to include an evaluation of the carbon intensity of H 2 production via electrolysis using nuclear power from LWRs. Finally, we examined the impact of future (2035 and 2050) electricity supply chain scenarios on nuclear fuel cycle GHG emissions. Our analysis revealed a decrease of 33% (2035) and 46% (2050) in the carbon intensity of nuclear electricity relative to current nuclear fuel cycle GHG emissions.

Complete genome sequence and genome organization of Ficus pumila-associated virus, a new putative member of the family Tymoviridae - Mengze Guo; Pingping Sun; Xudong Fan; Jianwei Guo; Lei Zhang; Zhengnan Li (Archives of Virology, 2025)

Elevated N2O emissions from coastal small water bodies: Implications for greenhouse gas inventories - Lele Tang; Wenjing Liu; Hong Yang; Ping Yang; Chuan Tong; Yongxin Lin; Dongyao Sun; Wenjing Tan; Wenbo Lin; Pingping Guo; Linhai Zhang; Kam W. Tang (Journal of Hydrology, 2025)

A GNSS PPP integrity monitoring algorithm based on ARKF and MHSS - Ershen Wang; Tengli Yu; Xinhui Sun; Pingping Qu; Tingyu Chen; Xuebao Hong; Song Xu; Zexin Liu (Advances in Space Research, 2025)

The capsid protein p72 specific mAb and the corresponding novel epitope based ELISAs for detection of ASFV infection - Jiajia Zhang; Ziyan Sun; Shaohua Sun; Kaili Zhang; Dafu Deng; Ping He; Pingping Zhang; Nengwen Xia; Sen Jiang; Wanglong Zheng; Francois Meurens; Jianzhong Zhu (Veterinary Microbiology, 2025)

Bayesian identification of the optimal soil-water characteristic curve (SWCC) model and reliability analysis of unsaturated loess slope from extremely sparse measurements - Tengyuan Zhao; Yabin Yang; Ling Xu; Pingping Sun (Engineering Geology, 2025)

Spatial Distribution and Quantitative Source Identification of Heavy Metals in Soil of a Typical Industrial Park, East of China - Shiyu Wang; Junnan Zhang; Jingyuan Sun; Fada Zhou; Pingping Wang; Zhirui Qin; Yue Zhao; Shuo Wang; Ziyu Han; Wentao Jiao (Bulletin of Environmental Contamination and Toxicology, 2025)

A nucleocapsid monoclonal antibody based sandwich ELISA for the general detection of both PRRSV-2 and PRRSV-1 - Shaohua Sun; Kaili Zhang; Jiajia Zhang; Ping He; Pingping Zhang; Dafu Deng; Chenglin Chi; Sen Jiang; Wanglong Zheng; Nanhua Chen; Jianzhong Zhu (Veterinary Microbiology, 2025)

Corrigendum to “Source and bioavailability of quaternary ammonium compounds (QACs) in dust: implications for nationwide exposure in China” [J Hazard Mater 480 (2024) 136268] - Yuhao Cao; Zhiguo Cao; Pingping Wang; Leicheng Zhao; Shaohan Zhang; Yumeng Shi; Lu Liu; Hongkai Zhu; Lei Wang; Zhipeng Cheng; Hongwen Sun (Journal of Hazardous Materials, 2025)

Independent temperature records since the last deglaciation from the varved sediments of Sihailongwan maar lake, northeastern China - Pingping Li; Guoqiang Chu; Patrick Rioual; Nan Zhan; Guibin Zhang; Zeyang Zhu; Li Qi; Manman Xie; Yuan Ling; Qing Sun (Quaternary Science Reviews, 2025)

Inversion of biophysical parameters of potato based on an active learning pool-based sampling strategy - Yuanyuan Ma; Xiaoyu Song; Jie Zhang; Di Pan; Haikuan Feng; Guijun Yang; Chunxia Qiu; Heguang Sun; Chunkai Zheng; Pingping Li (International Journal of Remote Sensing, 2025)

Source and bioavailability of quaternary ammonium compounds (QACs) in dust: Implications for Nationwide Exposure in China - Yuhao Cao; Zhiguo Cao; Pingping Wang; Leicheng Zhao; Shaohan Zhang; Yumeng Shi; Lu Liu; Hongkai Zhu; Lei Wang; Zhipeng Cheng; Hongwen Sun (Journal of Hazardous Materials, 2024)

Independent induction of calluses and nematophytes from exfronds and their potential application for kelp cultivation and germplasm conservation - Pingping Tian; Weiwei Wang; Yan Li; Guangjin Liang; Juan Sun; Yanling Liu; Guanpin Yang; Xiaojie Li (Journal of Applied Phycology, 2024)

The general patterns of water flow in loess slope system and implications for slope geological security - Li Feng; Maosheng Zhang; Hao Liu; Bin Zhang; Zhen Du; Pingping Sun; Junbo Bi; Liang Wang; Tianfeng Gu (Science of The Total Environment, 2024)

Incorporation crisis lifecycle theory into full-stage flash drought spatio-temporal pattern identification and risk analysis - Zixuan Qi; Yuchen Ye; Yanpeng Cai; Chaoxia Yuan; Yulei Xie; Guanhui Cheng; Pingping Zhang; Lian Sun (Journal of Hydrology, 2024)

Detecting thresholds in the health impact of the urban built environment - Wenyao Sun; Lan Wang; Arthi Rao; Steve Yim; Haidong Kan; Yue Gao; Surong Zhang; Catherine Ross; Bao Pingping (Applied Geography, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

Blending low-carbon hydrogen with natural gas: Impact on energy and life cycle emissions in natural gas pipelines - Vincenzo Cappello; Pingping Sun; Amgad Elgowainy (Gas Science and Engineering, 2024)

Analysis of Tidal Current Energy Potential in the Major Channels of the Bohai Strait Based on Delft3D - Pengcheng Ma; Hongyuan Shi; Huaiyuan Xue; Pingping Li; Yongkang Sun (Journal of Ocean University of China, 2024)

A novel yeast-based biosensor for the quick determination of Deoxynivalenol - Han Yang; Lianqun Du; Lu Geng; Xiao Liu; Zehua Xu; Ruonan Liu; Wentao Liu; Hu Zuo; Zongfen Chen; Xinyang Wang; Pingping Zhang; Tieqiang Sun (Analytica Chimica Acta, 2024)

Atmospheric water demand dominates terrestrial ecosystem productivity in China - You Tu; Xiaofeng Wang; Jitao Zhou; Xiaoxue Wang; Zixu Jia; Jiahao Ma; Wenjie Yao; Xinrong Zhang; Zechong Sun; Pingping Luo; Xiaoming Feng; Bojie Fu (Agricultural and Forest Meteorology, 2024)

Corrigendum to “Synergistic HA and NS mutations enhanced the virulence of a mouse-adapted H1N1 influenza A virus” [Veterin. Microbiol. 276 (2023) 109615] - Min Zhu; Jianqiao He; Hao Zeng; Pingping Wang; Yaohui Zhu; Fanyuan Sun; Xin Huang; Yi Xu; Chongqiang Huang; Jiancai Chen; Xinyi Guo; Huabo Zhou; et al. (Veterinary Microbiology, 2024)

Whether the development strategy of the Yangtze River Economic Belt can achieve the double welfare effects of synergistic governance of pollution control and carbon reduction? - Dongri Han; Pingping Sun; Caifeng Bi; Ziyi Shi (Urban Climate, 2024)

Identification of a novel waikavirus infecting Pittosporum tobira in China - Mengze Guo; Lei Zhang; Xudong Fan; Pingping Sun; Jianwei Guo; Zhengnan Li (Archives of Virology, 2024)

Dynamics of solar-induced chlorophyll fluorescence (SIF) and its response to meteorological drought in the Yellow River Basin - Hao Wu; Pingping Zhou; Xiaoyan Song; Wenyi Sun; Yi Li; Songbai Song; Yongqiang Zhang (Journal of Environmental Management, 2024)

Risk assessment and spatial analysis of paralytic shellfish toxin (PST) concentrations and acute dietary exposure of commercially available shellfish in coastal areas in China - Shuwen Li; Jiao He; Jinfang Sun; Feng Pan; Pingping Zhou; Lei Zhang; Xin Yang; Chengbin Cao; Xiaojin Yu; Pei Cao (Food Control, 2024)

Response of deep soil water deficit to afforestation, soil depth, and precipitation gradient - Jingxiong Zhou; Yunqiang Wang; Ruijie Li; Haoran He; Hui Sun; Zixuan Zhou; Yali Zhao; Pingping Zhang; Zimin Li (Agricultural and Forest Meteorology, 2024)

Development of an electrochemical separation-Rhodopseudomonas palustris electrolysis cell-coupled system for resourceful treatment of mature leachate landfill - Xiaoyan Bai; Yulang Huang; Jian Sun; Chunhua Feng; Yong Yuan; Qintie Lin; Kang Dai; Pingping Zhang (Journal of Environmental Management, 2024)

Ultrafine Ru nanoparticles stabilized by V8C7/C for enhanced hydrogen evolution reaction at all pH - Yanju Long; Yong Shen; Pingping Jiang; Hui Su; Jiahui Xian; Yamei Sun; Jun Yang; Haili Song; Qinghua Liu; Guangqin Li (Science Bulletin, 2024)

Industrializable and pH-tolerant electropositive imidazolium chloride polymer for high-efficiency removal of perfluoroalkyl carboxylic acids from aqueous solution - Xiaohui Wei; Pingping Liu; Danyang Bai; Luyuan Zhang; Hongyan Mao; Wenjing Zhang; Tianqi Chen; Dan Yin; Tianhua Sun; Yanhao Zhang; Wenfen Zhang (Journal of Hazardous Materials, 2024)

Peroxymonosulfate activation by walnut shell activated carbon supported nano zero-valent iron for the degradation of tetracycline: Performance, degradation pathway and mechanism - Pingping Duan; Fanlong Kong; Xiuzheng Fu; Zhijie Han; Guangwei Sun; Zhengda Yu; Sen Wang; Yuqian Cui (Environmental Research, 2024)

Intensive land restoration projects alter mechanisms underpinning spatiotemporal soil moisture variability at a catchment scale: A case study in China - Yali Zhao; Yunqiang Wang; Wei Hu; Hui Sun; Lijun Qi; Lan Xu; Yi Song; Pingping Zhang (Journal of Hydrology, 2024)

Investigating the long-term response of plateau vegetation productivity to extreme climate: insights from a case study in Qinghai Province, China - Hexuan An; Xiaoyan Song; Ziyin Wang; Xubo Geng; Pingping Zhou; Jun Zhai; Wenyi Sun (International Journal of Biometeorology, 2024)

Magnetically separable Co0.6Fe2.4O4/MIL-101-NH2 adsorbent for Congo red efficient removal - Zhenhong Zhang; Yuye Zhong; Peng Sun; Pingping Zhao; Houbin Li; Xinghai Liu (Environmental Science and Pollution Research, 2024)

Potato late blight severity monitoring based on the relief-mRmR algorithm with dual-drone cooperation - Heguang Sun; Xiaoyu Song; Wei Guo; Mei Guo; Yanzhi Mao; Guijun Yang; Haikuan Feng; Jie Zhang; Ziheng Feng; Jiao Wang; Yuanyuan Ma; Chunkai Zheng; et al. (Computers and Electronics in Agriculture, 2023)

Exploration of spatial heterogeneity in the effect of woodland proportion on PM2.5: An empirical study from the Yangtze River economic Belt, China - Min Wang; Yingmei Wu; Yang Wang; Pingping Hu; Guiquan Sun (Atmospheric Pollution Research, 2023)

Bibliometric evaluation of global research on eco-tourism - Han Lin; Yan Zhu; Zhoubao Sun; Pingping Wu; Jinjin Zhang (Environment, Development and Sustainability, 2023)

Porous pillararene-based polymer as adsorbent and solid disinfectant for water treatment - Guizhou Xu; Pingping Yang; Yalan Zhang; Lin Sun; Xuejiao Hu; Wenrui Zhang; Yizhou Tu; Yuansong Tian; Aimin Li; Xianchuan Xie; Xueyuan Gu (Chemosphere, 2023)

Impacts of ecological water supplement projects on fish habitat suitability in a high-leakage river in China - Xueping Gao; Luyao Zhang; Bowen Sun; Jiaxin Li; Pingping Miao; Yunpeng Bai (Journal of Hydrology, 2023)

Corrigendum to “Combining functional physiological phenotyping and simulation model to estimate dynamic water use efficiency and infer transpiration sensitivity traits” [Eur. J. Agron. 150 (2023) 126955] - Ting Sun; Rui Cheng; Rujia Jiang; Yunxiu Liu; Yudong Sun; Zhuoyi Wang; Pingping Fang; Xinyang Wu; Kang Ning; Pei Xu (European Journal of Agronomy, 2023)

Combining functional physiological phenotyping and simulation model to estimate dynamic water use efficiency and infer transpiration sensitivity traits - Ting Sun; Rui Cheng; Rujia Jiang; Yunxiu Liu; Yudong Sun; Zhuoyi Wang; Pingping Fang; Xinyang Wu; Kang Ning; Pei Xu (European Journal of Agronomy, 2023)

Regional spatial variability of soil organic carbon in 0–5 m depth and its dominant factors - Jingxiong Zhou; Yunqiang Wang; Yongping Tong; Hui Sun; Yali Zhao; Pingping Zhang (CATENA, 2023)

Distribution and Controlling Factors of Dissolved Gaseous Mercury and Reactive Mercury in Seawater Near Yangtze River Estuary - Pingping Yin; Wen Zheng; Yan Wang; Ruhai Liu; Xin He; Haolin Sun; Dou Li (Journal of Ocean University of China, 2023)

Efficacy of transplant insecticides against black cutworm Agrotis ipsilon (Lepidoptera: Noctuidae) in tobacco - Pingping Liu; Jingxin Zhang; Huifang Shen; Qiyun Yang; Xiaoming Pu; Dayuan Sun; Baiyi Ge; Birun Lin (Crop Protection, 2023)

Cost and life cycle analysis for deep CO2 emissions reduction of steelmaking: Blast furnace-basic oxygen furnace and electric arc furnace technologies - Guiyan Zang; Pingping Sun; Amgad Elgowainy; Pallavi Bobba; Colin McMillan; Ookie Ma; Kara Podkaminer; Neha Rustagi; Marc Melaina; Mariya Koleva (International Journal of Greenhouse Gas Control, 2023)

Repeated Digestion by Earthworms on Tetracycline Degrading and Biological Responses in Tetracycline-Contaminated Sewage Sludge - Ping Liu; Taotao Zha; Si-Qi Xia; Pingping Sun; Yu-Feng Wu; Haitao Zhao; Ke Feng (Water, Air, & Soil Pollution, 2023)

Speciation and source changes of atmospheric arsenic in Qingdao from 2016 to 2020 - Response to control policies in China - Haolin Sun; Yan Wang; Ruhai Liu; Pingping Yin; Dou Li; Long Shao (Chemosphere, 2023)

Synergistic HA and NS mutations enhanced the virulence of a mouse-adapted H1N1 influenza A virus - Min Zhu; Jianqiao He; Hao Zeng; Pingping Wang; Yaohui Zhu; Fanyuan Sun; Xin Huang; Yi Xu; Chongqiang Huang; Jiancai Chen; Xinyi Guo; Huabo Zhou; et al. (Veterinary Microbiology, 2023)

Assessment of heavy metals contamination and human health risk assessment of the commonly consumed medicinal herbs in China - Haiping Liu; Jianfeng Tang; Tongjun Chen; Pingping Zhu; Dongdong Sun; Weiyun Wang (Environmental Science and Pollution Research, 2023)

Application of resistivity measurement to stability evaluation for loess slopes - Bin Zhang; Li Feng; Maosheng Zhang; Pingping Sun; Tonglu Li; Hao Liu (Landslides, 2022)

Comparative transcriptome analysis unravels the response mechanisms of Cytospora mali QH2 to a biocontrol agent, Bacillus velezensis L-1 - Pingping Sun; Lei Zhang; Zhengnan Li (European Journal of Plant Pathology, 2022)

Cellular Heterogeneity Facilitates the Functional Differences Between Hair Follicle Dermal Sheath Cells and Dermal Papilla Cells: A New Classification System for Mesenchymal Cells within the Hair Follicle Niche - Yuyang Gan; Hailin Wang; Lijuan Du; Kaitao Li; Qian Qu; Weiwen Liu; Pingping Sun; Zhexiang Fan; Jin Wang; Ruosi Chen; Zhiqi Hu; Yong Miao (Stem Cell Reviews and Reports, 2022)

Complete genomic characterization of a reassortment isolate of Sophora yellow stunt virus from Sophora alopecuroides in China - Shuang Song; Pingping Sun; Mingxiu Ju; Xuan Zhang; Xingqi Yang; Lei Zhang; Zhengnan Li (Journal of Plant Pathology, 2022)

Dexmedetomidine post-conditioning alleviates myocardial ischemia–reperfusion injury in rats by ferroptosis inhibition via SLC7A11/GPX4 axis activation - Peng Yu; Jing Zhang; Yi Ding; Dandan Chen; Haijian Sun; Fenglai Yuan; Siyuan Li; Xiaozhong Li; Pingping Yang; Linghua Fu; Shuchun Yu; Jiru Zhang (Human Cell, 2022)

Brain functional specialization and cooperation in Parkinson’s disease - Jinmei Sun; Xiaoran Gao; Qiang Hua; Rongrong Du; Pingping Liu; Tingting Liu; Jinying Yang; Bensheng Qiu; Gong-Jun Ji; Panpan Hu; Kai Wang (Brain Imaging and Behavior, 2022)

Mutant library resources for legume crops and the emerging new screening technologies - Wenjun Xia; Peipei Zhang; Xinyang Wu; Mingxuan Li; Ting Sun; Pingping Fang; Arun K. Pandey; Pei Xu (Euphytica, 2022)

Prenatal diagnosis of the Dandy–Walker malformation associated with partial trisomy 12p and distal 15q deletion - Yanmei Sun; Ning Zhang; Haishen Tian; Pingping Zhang; Yali Li (Journal of Genetics, 2021)

Omics resources and omics-enabled approaches for achieving high productivity and improved quality in pea (Pisum sativum L.) - Arun K. Pandey; Diego Rubiales; Yonggang Wang; Pingping Fang; Ting Sun; Na Liu; Pei Xu (Theoretical and Applied Genetics, 2021)

Plant gasotransmitters: light molecules interplaying with heavy metals - Pingping Fang; Ting Sun; Yonggang Wang; Yanfei Ding; Arun Kumar Pandey; Cheng Zhu; Pei Xu (Reviews in Environmental Science and Bio/Technology, 2021)

Occurrence and molecular variability of apple-associated Luteovirus isolates from apple in China based on coat protein genes - Zhengnan Li; Mingxiu Ju; Lei Zhang; Mengji Cao; Pingping Sun (European Journal of Plant Pathology, 2021)

Development and application of a comparative risk assessment method for ranking chemical hazards in food - Ying Li; Guoxin Liang; Lei Zhang; Zhaoping Liu; Dajin Yang; Jianwen Li; Guiju Sun; Pingping Zhou (Food Additives & Contaminants: Part A, 2021)

Prenatal diagnosis and neonatal phenotype of a de novo microdeletion of 17p11.2p12 associated with Smith‒Magenis syndrome and external genital defects - Pingping Zhang; Yanmei Sun; Haishen Tian; Limin Rong; Fangna Wang; Xiaoping Yu; Yali Li; Jian Gao (Journal of Genetics, 2020)

Deciphering p53 dynamics and cell fate in DNA damage response using mathematical modeling - Nanfei Yang; Tingzhe Sun; Pingping Shen (Genome Instability & Disease, 2020)

Correction to: B7-H3 modulates endothelial cell angiogenesis through the VEGF cytokine - Huijun Lai; Zhongwen Sun; Jie Yang; Pingping Wu; Yundi Guo; Jing Sun (Immunologic Research, 2020)

Risk grade assessment of sudden water pollution based on analytic hierarchy process and fuzzy comprehensive evaluation - Hao Zhang; Wenjun Li; Pingping Miao; Bowen Sun; Fanqing Kong (Environmental Science and Pollution Research, 2020)

Reactive oxygen species induced by personal exposure to fine particulate matter emitted from solid fuel combustion in rural Guanzhong Basin, northwestern China - Yaqi Li; Hongmei Xu; Kailai He; Jinhui Wang; Zhi Ning; Qiyuan Wang; Nan Li; Zhenxing Shen; Pingping Liu; Jian Sun; Xinyi Niu; Yongxiao Cao; et al. (Air Quality, Atmosphere & Health, 2019)

Correction to: In Vitro Seeding Activity of Glycoform-Deficient Prions from Variably Protease-Sensitive Prionopathy and Familial CJD Associated with PrPV180I Mutation - Zerui Wang; Jue Yuan; Pingping Shen; Romany Abskharon; Yue Lang; Johnny Dang; Alise Adornato; Ling Xu; Jiafeng Chen; Jiachun Feng; Mohammed Moudjou; Tetsuyuki Kitamoto; et al. (Molecular Neurobiology, 2019)

In Vitro Seeding Activity of Glycoform-Deficient Prions from Variably Protease-Sensitive Prionopathy and Familial CJD Associated with PrPV180I Mutation - Zerui Wang; Jue Yuan; Pingping Shen; Romany Abskharon; Yue Lang; Johnny Dang; Alise Adornato; Ling Xu; Jiafeng Chen; Jiachun Feng; Mohammed Moudjou; Tetsuyuki Kitamoto; et al. (Molecular Neurobiology, 2019)

ALIX increases protein content and protective function of iPSC-derived exosomes - Ruiting Sun; Yingying Liu; Meng Lu; Qianqian Ding; Pingping Wang; Heng Zhang; Xiaoyu Tian; Peng Lu; Dan Meng; Ning Sun; Meng Xiang; Sifeng Chen (Journal of Molecular Medicine, 2019)

B7-H3 modulates endothelial cell angiogenesis through the VEGF cytokine - Huijun Lai; Zhongwen Sun; Jie Yang; Pingping Wu; Yundi Guo; Jing Sun (Immunologic Research, 2019)

Natural and synthetic flavonoids, novel blockers of the volume-regulated anion channels, inhibit endothelial cell proliferation - Yucong Xue; Honglin Li; Yuanyuan Zhang; Xue Han; Gaohua Zhang; Wenya Li; Huiran Zhang; Yue Lin; Pingping Chen; Xiaorun Sun; Yalei Liu; Li Chu; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

In vitro genotoxicity of asbestos substitutes induced by coupled stimulation of dissolved high-valence ions and oxide radicals - Tingting Huo; Faqin Dong; Jianjun Deng; Qingbi Zhang; Wei Ye; Wei Zhang; Pingping Wang; Dongping Sun (Environmental Science and Pollution Research, 2018)

Transcriptomic analysis reveals the effect of the exopolysaccharide of Psychrobacter sp. B-3 on gene expression in RAW264.7 macrophage cells - Pingping Zhang; Jiang Li; Leiye Yu; Jingfang Wei; Tong Xu; Guojie Sun (Acta Oceanologica Sinica, 2018)

Colon-Targeted Delivery of IgY Against Clostridium difficile Toxin A and B by Encapsulation in Chitosan-Ca Pectinate Microbeads - Pingping Xing; Yanan Shi; Chuangchuang Dong; Hong Liu; Yan Cheng; Junbo Sun; Dalei Li; Min Li; Kaoxiang Sun; Dongxiao Feng (AAPS PharmSciTech, 2017)

Increased Active Tumor Targeting by An αvβ3-Targeting and Cell-Penetrating Bifunctional Peptide-Mediated Dendrimer-Based Conjugate - Pengkai Ma; Huajun Yu; Xuemei Zhang; Hongjie Mu; Yongchao Chu; Ling Ni; Pingping Xing; Yiyun Wang; Kaoxiang Sun (Pharmaceutical Research, 2017)

Extending the linker region increases the activity of the Bacillus subtilis cellulase CelI15 - Pingping Li; Yang Zhou; Qian Li; Chong Zhang; Zhaowei Sun; Liuyang Tian; Haibo Weng (Biotechnology Letters, 2016)

A stable isotope approach and its application for identifying nitrate source and transformation process in water - Shiguo Xu; Pingping Kang; Ya Sun (Environmental Science and Pollution Research, 2016)

A novel l-asparaginase from Aquabacterium sp. A7-Y with self-cleavage activation - Zhibin Sun; Ding Li; Pingping Liu; Wenhui Wang; Kai Ji; Yan Huang; Zhongli Cui (Antonie van Leeuwenhoek, 2016)

A novel dual EGFR/HER2 inhibitor KU004 induces cell cycle arrest and apoptosis in HER2-overexpressing cancer cells - Chongchong Tian; Pingping Ding; Ziqiao Yuan; Han Li; Yanxia Zhao; Lan Sun; Qingming Guo; Zhenzhong Wang; Lixin Sun; Luyong Zhang; Zhenzhou Jiang (Apoptosis, 2015)

Transcriptomic Analyses Reveal Novel Genes with Sexually Dimorphic Expression in Yellow Catfish (Pelteobagrus fulvidraco) Brain - Jianguo Lu; Min Zheng; Jiajia Zheng; Jian Liu; Yongzhuang Liu; Lina Peng; Pingping Wang; Xiaofeng Zhang; Qiushi Wang; Peixian Luan; Shahid Mahbooband; Xiaowen Sun (Marine Biotechnology, 2015)

Isolation and characterization of a proteinaceous α-amylase inhibitor AAI-CC5 from Streptomyces sp. CC5, and its gene cloning and expression - Zhibin Sun; Weihao Lu; Pingping Liu; Hui Wang; Yan Huang; Yuguo Zhao; Yi Kong; Zhongli Cui (Antonie van Leeuwenhoek, 2015)

The Roles of p38 MAPK/MSK1 Signaling Pathway in the Neuroprotection of Hypoxic Postconditioning Against Transient Global Cerebral Ischemia in Adult Rats - Pingping Zhu; Lixuan Zhan; Tingna Zhu; Donghai Liang; Jiaoyue Hu; Weiwen Sun; Qinghua Hou; Huarong Zhou; Baoxing Wu; Yanmei Wang; En Xu (Molecular Neurobiology, 2014)

Geochronologic-petrochemical studies of the Hongshishan mafic–ultramafic intrusion, Beishan area, Xinjiang (NW China): petrogenesis and tectonic implications - Benxun Su; Kezhang Qin; Patrick Asamoah Sakyi; Dongmei Tang; Pingping Liu; Sanjeewa P.K. Malaviarachchi; Qinghua Xiao; He Sun (International Geology Review, 2012)

Olivine compositional mapping of mafic-ultramafic complexes in eastern Xinjiang (NW China): Implications for Cu-Ni mineralization and tectonic dynamics - Benxun Su; Kezhang Qin; He Sun; Dongmei Tang; Qinghua Xiao; Pingping Liu; Patrick Asamoah Sakyi (Journal of Earth Science, 2012)

Cell-death-mode switch from necrosis to apoptosis in hydrogen peroxide treated macrophages - XuZhu Lin; TingZhe Sun; MeiHong Cai; PingPing Shen (Science China Life Sciences, 2010)